METHOD FOR PARAMETERS ESTIMATION OF AVIATION SATELLITE COMMUNICATION CHANNEL - Kharchenko, Volodymyr; Grekhov, Andrii; Ali, Ismail (Proceedings of National Aviation University (archive), 2015)
For estimation of satellite OFDM communication channel parameters the original model of a channel "Aircraft-Satellite-Ground Station" with adaptive modulation was built using MATLAB Sіmulіnk software. Model consists of a source of information, an aircraft transmitter, an uplink/downlink path, a satellite transponder, and a ground station receiver. The dependencies of a signal to noise ratio on free space path loss for different types of modulation (BPSK, QPSK, 16QAM, 64QAM), noise temperatures, number of OFDM symbols, frequency offsets, satellite amplifier linear gain, and aircraft antenna diameter were received and analyzed. A method for parameters estimation of satellite OFDM communication channel was developed.